The Influence of Managerial Decisions, Ethical Orientation, and Locus of Control on Whistleblowing Intentions in Preventing Fraud in MSMEs - Fanny Evanda Fachruddin; Novi Darmayanti; Isnaini Anniswati Rosyida (LP2M IAIN Palopo, 2026)
The primary purpose of this study is to analyze the impact of managerial decisions, ethical orientation, and locus of control on whistleblowing intentions in preventing fraud in MSMEs in Bojonegoro Regency. This studi is grounded in a quantitative methodology, with data collection carried out through a structured survey. The data sources' firsthand information was gathered using a set of questionnaire items directed at the respondents to MSMEs owners and employees involved in operational activities in Bojonegoro Regency. A non-probability sampling method, specifically purposive sampling, resulted in a total of 103 participants who met the research criteria. Data processing and analysis were conducted using multiple regression analysis methods in IBM SPSS Statistics version 31. Based on the partial test results, ethical orientation and locus of control exert a positive influence on whistleblowing intentions, while managerial decisions fail to notably impact whistleblowing intentions. These findings indicate that the stronger an individual's ethical orientation and locus of control, the greater their willpower to engage in report as an effort to prevent fraud in MSMEs